2020
DOI: 10.30802/aalas-jaalas-20-000018
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia During General Anesthesia Interferes with Pain Assessment in Laboratory Rats (Rattus norvegicus)

Abstract: Accurate pain assessment methods are necessary to ensure animal welfare and reliable data collection in animal research.The Rat Grimace Scale (RGS), a facial expression pain scale, allows effective identification of pain. However, the potentialconfounds of this method remain mostly unexplored. General anesthesia, which is used in many laboratory procedures,suppresses thermoregulation and results in hypothermia. We investigated the effects of isoflurane-induced hypothermia onRGS scores. Twenty (10 male and 10 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Similarly, some cats undergoing sedation and general anesthesia may experience mildly increased facial grimace scores for up to 30 min following anesthesia 87 . No specific mechanism was proposed for either of these induced grimace score alterations and the presence of hypothermia (a condition commonly occurring during anesthesia and surgery of animals and associated with increased grimace scores in a rat study 88 ) was also not reported, so it is unknown whether the changes were induced directly by anesthesia or because of other alterations in physiologic state,. Although the current study did not evaluate macaques until at least 2 h following general anesthesia further research is needed to determine whether and if inhalant or injectable anesthetics have an effect on CMGS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some cats undergoing sedation and general anesthesia may experience mildly increased facial grimace scores for up to 30 min following anesthesia 87 . No specific mechanism was proposed for either of these induced grimace score alterations and the presence of hypothermia (a condition commonly occurring during anesthesia and surgery of animals and associated with increased grimace scores in a rat study 88 ) was also not reported, so it is unknown whether the changes were induced directly by anesthesia or because of other alterations in physiologic state,. Although the current study did not evaluate macaques until at least 2 h following general anesthesia further research is needed to determine whether and if inhalant or injectable anesthetics have an effect on CMGS scores.…”
Section: Discussionmentioning
confidence: 99%
“… 289 In addition, hypothermia during rodent anesthesia is common 137 and has recently been shown to interfere with post-operative pain assessments. 290 Thus, it is widely accepted that most procedures involving rodent sedation or general anesthesia include normothermia support and the shortest duration possible. However, in cases of prolonged anesthesia duration, the anesthesia duration effects as a research variable must be addressed.…”
Section: Factors Affecting Anesthesiamentioning
confidence: 99%
“…In human patients, hypothermia is linked to the need for more postoperative analgesia 50,51 . Similarly, hypothermia in rats results in a more significant proportion of rats crossing a predetermined analgesic intervention threshold 52 . Furthermore, hypothermia induced by isoflurane anesthesia confounds accurate Rat Grimace Scale scoring, a facial expression pain scale allowing effective identification of pain 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, hypothermia in rats results in a more significant proportion of rats crossing a predetermined analgesic intervention threshold 52 . Furthermore, hypothermia induced by isoflurane anesthesia confounds accurate Rat Grimace Scale scoring, a facial expression pain scale allowing effective identification of pain 52 . Also, hypothermia is linked to shivering during anesthesia recovery to increase core body temperature, which may cause damage to the surgical site and contribute to postoperative pain 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation